Interaction of PLS and PIN and hormonal crosstalk in Arabidopsis root development - Liu, Junli; Mehdi, Saher; Topping, Jennifer; Friml, Jiri; Lindsey, Keith (Frontiers in Plant Science, 2013)
Understanding how hormones and genes interact to coordinate plant growth is a major challenge in developmental biology. The activities of auxin, ethylene and cytokinin depend on cellular context and exhibit either synergistic or antagonistic interactions. Here we use experimentation and network construction to elucidate the role of the interaction of the POLARIS peptide (PLS) and the auxin efflux carrier PIN proteins in the crosstalk of three hormones (auxin, ethylene and cytokinin) in Arabidopsis root development. In ethylene hypersignalling mutants such as polaris (pls), we show experimentally that expression of both PIN1 and PIN2 significantly increases. This relationship is analysed in the context of the crosstalk between auxin, ethylene and cytokinin: in pls, endogenous auxin, ethylene and cytokinin concentration decreases, approximately remains unchanged and increases, respectively. Experimental data are integrated into a hormonal crosstalk network through combination with information in literature. Network construction reveals that the regulation of both PIN1 and PIN2 is predominantly via ethylene signalling. In addition, it is deduced that the relationship between cytokinin and PIN1 and PIN2 levels implies a regulatory role of cytokinin in addition to its regulation to auxin, ethylene and PLS levels. We discuss how the network of hormones and genes coordinates plant growth by simultaneously regulating the activities of auxin, ethylene and cytokinin signalling pathways.